The Management of Marine Pollution in Straits That Used For International Shipping Based on the Law of the Sea Convention 1982 in Indonesia - Sudini, Luh Putu (Institute of Research and Community Service, University of Brawijaya, 2015)
Density of crossing vessels in straits used for international navigation, such as in the Malacca Strait, allows the occurrence of serious pollution of sea water in the strait. In addressing marine pollution in straits used for international navigation in Indonesia, it is necessary to the management arrangements of marine pollution in straits used for international navigation in Indonesia. In connection with the management of marine pollution in straits used for international navigation, it is deemed necessary to have the ideal management of marine pollution in straits used for international navigation in Indonesia.This research is a law that is normative by using a main approach of legislation, with a source of legal materials through library research.Indonesia has ratified the Convention 1982 on the Law of the Sea through Act No. 17 of 1985; therefore, the Indonesian government should establish law as a legal product that regulates Indonesia as an archipelagic State traveled its waters by foreign ships of the easy and high chance in causing sea pollution. The concept of the ideal management of marine pollution in straits used for international navigation is integrated and coordinated by the agency related to the marine pollution in Indonesia. By using the marine pollution liability compensation to the principle of strict liability, it could beneficial for the injured party due to marine pollution. It is expected that the Indonesian government immediately establishes statutory laws and regulations relating to the management of pollution at sea; the academics at universities participating socializing marine management in particular marine pollution from shipping foreign vessels in Indonesian waters.Â Keyword :Â Management of Marine Pollution;Â Straits Used for International Shipping; Convention 1982 on the Law of the Sea; Indonesia